Penggunaan Teknik Blok Perifer Angkle pada Pasien Papo Digiti 4,5 Pedis Sinistra - Triputra, Audhiaz Marthsyal; Mahmud; Artika, I Gusti Ngurah Rai (Jurnal Komplikasi Anestesi, 2018)
A 75 yearl old woman diagnosed gangrenous 4th – 5th left digiti pedis e.c susp. PAPO went to surgery with amputation of the 4th and 5th left digiti pedis with a peripheral nerve block anesthesia techniques. Preoperative physical status been classified with ASA II, with warfarin therapy has been discontinued since 4 days ago and replaced with UF heparin for one day therapy. The operation takes approximately less than one hour with hemodynamically stable, patients had no complaints of pain to post-surgery. Heparin therapy then continued one day after surgery